(untitled) (Journal of actual problems of jurisprudence, 2023)
The relevance of the study is due to the issues of the operation of the principles of mediation as one of the alternative ways to resolve disputes in the Republic of Kazakhstan. In this regard, the purpose of the work is to identify problems with the operation of the principles during the mediation procedure. When writing a research paper, the methods of logical analysis, dogmatic, formal legal, deductive, synthesis and other methods were used. The article discusses the features of the concept of mediation as an alternative method of resolving disputes in the works of legal scholars. The guiding norms of law that determine the content and directions of legal regulation are considered, i.e., the principles of intermediary services are explained and their types are considered. Although mediation has not developed rapidly in the Republic of Kazakhstan over the past decade, it should be noted that it is developing in many areas of society as an alternative method of dispute resolution. Since mediation is a procedure based only on certain principles, there should be no problems in the functioning of the principles. In accordance with this, the opinions of scientists are analyzed, a review of international acts is carried out, the principles of the current law "On Mediation" in the Republic of Kazakhstan are differentiated, and some recommendations are given on their application in practice. The practical value of the results obtained lies in providing ways to resolve problematic aspects that will have an impact on improving efficiency in law enforcement practice. Keywords: institution of mediation, mediation, mediator, disputes, voluntariness, confidentiality.